2020
DOI: 10.1113/jp279810
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microRNA‐221, ‐222, ‐21 and ‐27 in articular cartilage subjected to abnormal compressive forces

Abstract: r microRNAs (miRs) are small non-coding molecules that regulate post-transcriptional target gene expression. r miRs are involved in regulating cellular activities in response to mechanical loading in all physiological systems, although it is largely unknown whether this response differs with increasing magnitudes of load. r miR-221, miR-222, miR-21-5p and miR-27a-5p were significantly increased in ex vivo cartilage explants subjected to increasing load magnitude and in in vivo joint cartilage exposed to abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Preceding results showed EVs secreted by chondrocytes contained miR-221-3p, the expression level was consistent with the maternal cells [48] and it changed with mechanical loading [16,30]. To simulate the interface between cartilage and bone, and to evaluate how the miR-221-3p secreted by chondrocytes can potentially affect the bone formation capacity of osteoblasts, we cocultured these two cells in an in vitro model and found that the signal of overexpressed miR-221-3p in chondrocytes was transferred to osteoblasts with inhibited osteogenic markers expression of COL1A1 and RUNX2 (Figure 6a-b), while the OCN (Figure 6c), a late marker for bone formation [49], was not inhibited.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Preceding results showed EVs secreted by chondrocytes contained miR-221-3p, the expression level was consistent with the maternal cells [48] and it changed with mechanical loading [16,30]. To simulate the interface between cartilage and bone, and to evaluate how the miR-221-3p secreted by chondrocytes can potentially affect the bone formation capacity of osteoblasts, we cocultured these two cells in an in vitro model and found that the signal of overexpressed miR-221-3p in chondrocytes was transferred to osteoblasts with inhibited osteogenic markers expression of COL1A1 and RUNX2 (Figure 6a-b), while the OCN (Figure 6c), a late marker for bone formation [49], was not inhibited.…”
Section: Discussionmentioning
confidence: 69%
“…However, these studies have exclusively focused on the role of EVs on cartilage, despite the significance of the adjacent subchondral bone in the context of osteoarthritis [24]. Experimental evidence showed the mechanosensitive nature of miR-221 [16,29,30] and a paracrine effect from chondrocyte to chondrocyte [8] acting mainly on proliferation inside the same tissue. In this study, we demonstrate that chondrocyte derived EVs can inhibit the function of a completely different cell type (osteoblast) in a different tissue (bone), thereby establishing trans-tissue communication.…”
Section: Discussionmentioning
confidence: 99%
“…The described upregulation of GLI3 in OA cartilage with the here-observed negative correlation would indeed be in line with a potential beneficial role for miRNA-181a-5p in cartilage homeostasis. Finally, miR-221-5p, previously found to be upregulated in lesioned as compared to preserved OA cartilage [ 19 ], and now shown to have predictive potential for OA progression, was shown to be induced in response to mechanical loading of bovine and mouse cartilage [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are small non-coding RNAs involved in a wide range of biological regulatory processes; a number of studies have shown that numerous miRNAs play important roles in mechanical regulation (14,17) Under microgravity, the mechanosensory miR-103 is upregulated and may inhibit bone formation by targeting runt-related transcription factor 2 (Runx2) during osteoblast differentiation (18). Coincidentally, miR-103 inhibits osteoblast proliferation and bone formation mainly by suppressing the expression of the calcium channel voltage-dependent L type a 1C subunit, which encodes Cav1.2 under reduced load conditions (19).…”
Section: Tail Suspension Delays Ectopic Ossification In Proteoglycan-induced Ankylosing Spondylitis In Mice Via Mir-103/dkk1mentioning
confidence: 99%